Training on Strengthening Mastery of the Merdeka Mengajar Platform for SD Inpres 3 Talise Teachers to Create a Positive School Culture: Pelatihan Penguatan Penguasaan Platform Merdeka Mengajar (PMM) Guru SD Inpres 3 Talise untuk Menciptakan Budaya Sekolah yang Positif - Andi Patmasari; Muhammad Ismail; Andi Saadillah; Wilda Utami; Hijrinia Kusumaning Ayu; Dewi Satria Ahmar (Yayasan Ahmar Cendekia Indonesia, 2024)
Enhancing teachers’ ability to use Merdeka Curriculum and establish a nurturing learning environment is the aim of community service. The training activities include observation, socializing, material provision, practical experience, assessment, and reflection. Teachers who complete this program will be able to utilize the Merdeka Mengajar Platform to develop comprehensive lesson plans and assessments that align with the ideas of flexible and student-focused learning. According to the evaluation’s findings, 84% of teachers are able to utilize the platform on their own, and 87.5% of teachers effectively applied the Merdeka Curriculum with an average score of 3.50. Still, some educators require ongoing assistance. With ongoing support, it is envisaged that the training’s outcomes would enhance instruction quality and overall student learning outcomes.